Zooplankton Are Not Fish: Improving Zooplankton Realism in Size-Spectrum Models Mediates Energy Transfer in Food Webs - Heneghan, Ryan F.; Everett, Jason D.; Blanchard, Julia L.; Richardson, Anthony J. (Frontiers in Marine Science, 2016)
The evidence for an equal distribution of biomass from bacteria to whales has led to development of size-spectrum models that represent the dynamics of the marine ecosystem using size rather than species identity. Recent advances have improved the realism of the fish component of the size-spectrum, but these often assume that small fish feed on an aggregated plankton size-spectrum, without any explicit representation of zooplankton dynamics. In these models, small zooplankton are grouped with phytoplankton as a resource for larval fish, and large zooplankton are parameterized as small fish. Here we investigate the impact of resolving zooplankton and their feeding traits in a dynamic size-spectrum model. First, we compare a base model, where zooplankton are parameterized as smaller fish, to a model that includes zooplankton-specific feeding parameters. Second, we evaluate how the parameterization of zooplankton feeding characteristics, specifically the predator-prey mass ratio (PPMR), assimilation efficiency and feeding kernel width, affects the productivity and stability of the fish community. Finally, we compare how feeding characteristics of different zooplankton functional groups mediate increases in primary production and fishing pressure. Incorporating zooplankton-specific feeding parameters increased productivity of the fish community, but also changed the dynamics of the entire system from a stable to an oscillating steady-state. The inclusion of zooplankton feeding characteristics mediated a trade-off between the productivity and resilience of the fish community, and its stability. Fish communities with increased productivity and lower stability were supported by zooplankton with a larger PPMR and a narrower feeding kernel – specialized herbivores. In contrast, fish communities that were stable had lower productivity, and were supported by zooplankton with a lower PPMR and a wider feeding kernel – generalist carnivores. Herbivorous zooplankton communities were more efficient at mediating increases in primary production, and supported fish communities more resilient to fishing. Our results illustrate that zooplankton are not just a static food source for larger organisms, nor can they be resolved as very small fish. The unique feeding characteristics of zooplankton have enormous implications for the dynamics of marine ecosystems, and their representation is of critical importance in size-spectrum models, and end-to-end ecosystem models more broadly.